Psychopath [compact disc] - Wade, Morgan, 1994- (Ladylike Records ; RCA, 2023)
An astounding 13-track LP crafted with the help of some of Nashville's most extraordinary musical talents, from A-list songwriters to studio musicians and, of course, her longtime producer guru/song whisperer Sadler Vaden, this album most excitingly finds Wade peeling back layers of her psyche like never before.